The Effect Of Addition Of Castor Oil, Grape Seed Oil And Fenugreek Oil On Some Properties Of Cold Cure Acrylic Resin Denture Base Material. - Amer A. Taqa; Saja A. A; Myada M.Ali (University of Mosul, College of Dentistry, 2015)
Aims: The aim of the study is to evaluate the effect of addition of some natural and beneficial oils (Castor oil, Grape seed oil and Fenufreek oil) in different concentrations (1.5%,2%,2.5%) on some properties (chemical structure, residual monomer, transverse strength and color change) of cold cured acrylic resin. Materials & Method: One hundred samples were prepared from Respal cold cured acrylic resin.Ten samples were the control, thirty samples were prepared with addition of each oil (ten samples for each concentration). Each group of samples were evaluated for chemical structure (by Fourier Transform Infrared Spectrophotometer), residual monomer (by U.V. spectrophotometer), transverse strength (by instron testing machine) and color change by (Vita easy-shade).Results: the results were analysed statistically by ANOVA and Duncan's multiple range test. Conclusion: it's shown that the Castor oil additive (2.5%) showed decrease in the residual monomer release and not significant difference in transverse strength, lightness, chroma and hue from the standard group.